2010
DOI: 10.1186/1471-2458-10-624
|View full text |Cite
|
Sign up to set email alerts
|

Measuring newborn foot length to identify small babies in need of extra care: a cross sectional hospital based study with community follow-up in Tanzania

Abstract: BackgroundNeonatal mortality because of low birth weight or prematurity remains high in many developing country settings. This research aimed to estimate the sensitivity and specificity, and the positive and negative predictive values of newborn foot length to identify babies who are low birth weight or premature and in need of extra care in a rural African setting.MethodsA cross-sectional study of newborn babies in hospital, with community follow-up on the fifth day of life, was carried out between 13 July an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
59
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 21 publications
(29 reference statements)
18
59
3
Order By: Relevance
“…In newborns <2.0 kg group Sarlahi et al had cut off Foot length <6.9 cm, whereas in our study it was 7.4 cm. In newborns <2.5 kg group Mathur et al 12 had cut off Foot length <7.2cm, Hirve et al 10 had <7.6 cm(wt 1.5-2.5 kg) , Mukherjee et al 11 7.9 cm ,whereas in our case it was 8.2 cm.Sensitivity & specificity of foot length for birth wt < 1.5 kg , was 100% & 95.2% in Hirve et al 10 ,75% & 99 % in Marchant et al 9 , 100% and 95% in Mukherjee et al 11 and in our study it was 92% and 87% respectively. In our study Foot length had highest correlation with birth weight ( r=0.96), followed by head circumference (r=0.88),chest circumference(r=0.82), calf circumference(r=0.76) and length (r=0.65), Elizabeth et al 8 had also highest correlation of Foot length with birth weight (r=0.97) like us and head circumference (r=0.88), however Foot length had higher correlation with chest circumference in their study (r= 0.93) whereas in our study it was lower (r=0.82).…”
Section: Discussionsupporting
confidence: 48%
“…In newborns <2.0 kg group Sarlahi et al had cut off Foot length <6.9 cm, whereas in our study it was 7.4 cm. In newborns <2.5 kg group Mathur et al 12 had cut off Foot length <7.2cm, Hirve et al 10 had <7.6 cm(wt 1.5-2.5 kg) , Mukherjee et al 11 7.9 cm ,whereas in our case it was 8.2 cm.Sensitivity & specificity of foot length for birth wt < 1.5 kg , was 100% & 95.2% in Hirve et al 10 ,75% & 99 % in Marchant et al 9 , 100% and 95% in Mukherjee et al 11 and in our study it was 92% and 87% respectively. In our study Foot length had highest correlation with birth weight ( r=0.96), followed by head circumference (r=0.88),chest circumference(r=0.82), calf circumference(r=0.76) and length (r=0.65), Elizabeth et al 8 had also highest correlation of Foot length with birth weight (r=0.97) like us and head circumference (r=0.88), however Foot length had higher correlation with chest circumference in their study (r= 0.93) whereas in our study it was lower (r=0.82).…”
Section: Discussionsupporting
confidence: 48%
“…The following devices were used: KL-218 digital weighing scale (precision 10g; Dongguan Manufacturing, Hong Kong, China), JiVitA infant length board (JiVitA, Gaibandha, Bangladesh), 25,26 and JiVitA measuring tape (JiVtA). 26 Foot length was measured from base of the heel to tip of the hallux with a clear plastic metric ruler (locally purchased, Sylhet, Bangladesh) using methods described by Marchant et al 12 A total of 24 CHWs were trained and standardized in the newborn assessment (detailed in the text of the Supplemental Information). Refresher training was conducted after 6 months.…”
Section: Neonatal Assessmentmentioning
confidence: 99%
“…Simplified methods to identify premature infants that rely on fewer characteristics, 7 external signs only, 8,9 or individual physical anthropometrics [10][11][12] have been described and developed for lower resource settings. The Eregie, Capurro, and Parkin scores (Supplemental Table 5) have been reported to estimate GA in high correlation with the Dubowitz score.…”
mentioning
confidence: 99%
“…In Brazil, the percentage of infant births with low birth weight has increased slightly from 7.7% in 2000 to 8.5% in 2011 (16) . In a hospital-based recruitment conducted in Tanzania, a 15% prevalence of LBW infants was identified (17) . On the other hand, a study developed in Uganda showed a slightly lower percentage of LBW, being 12% (7) .…”
Section: Discussionmentioning
confidence: 99%
“…The ideal maximum period to perform HCL measurement is still controversial. Some authors state that HCL maintains a strong correlation with weight from birth up to the fifth day after birth, being a good predictor for the evaluation of low birth weight (16)(17)(18) . However, a study revealed that newborn's feet significantly increase in length/size during the first five days of life, suggesting that further research needs to be developed to determine the maximum period for this measure (7) .…”
Section: Discussionmentioning
confidence: 99%